Composition for fired body and method for producing fired body using the same
Patent Information
- Application Number
- JP2023142618
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-02
- Publication Date
- 2025-03-14
AI Technical Summary
【0031】 本発明は、煩雑な工程を経ることなく、簡単な製造方法で高炉スラグ(a)、下水汚泥焼却灰(b)と、エコスラグ粗粒(c)、エコスラグ細粒(e)を原料として焼成用組成物を構成でき、例えば、大気下の焼成条件で、比重2.3以上の焼成体で、吸水率4%以下、好ましくは1%以下、12mm程度径の球体で、圧壊強度は、2000N以上で、好ましくは2450N以上の人工骨材や、大気下の焼成条件で、吸水率10%以下の、実用強度の土木建築資材が得られる。
Smart Images

Figure 2025035534000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition for a sintered body and a method for producing a sintered body using the same. In particular, the present invention relates to a composition for a sintered body using industrial waste such as blast furnace slag, eco-slag, and sewage sludge incineration ash, and a method for producing a sintered body using the same. [Background technology]
[0002] Blast furnace slag has latent hydraulic properties, reacts with water and hardens, and its strength improves over time, so it can be expected to have a high bearing capacity, and there is no risk of an alkali-aggregate reaction.Furthermore, since it does not contain clay or organic impurities, it can be used as a coarse aggregate for concrete just like natural aggregate, and its use as a fine aggregate for concrete is also increasing.It is also used as a roadbed material, etc.
[0003] According to the definition of the Ministry of Land, Infrastructure, Transport and Tourism, "Eco-slag is molten slag made by burning organic matter, mainly general waste (urban waste), sewage sludge or their incineration ash, under high-temperature conditions of approximately 1,200°C or higher, melting inorganic matter, and then cooling it to produce a glassy or crystalline solidified material."
[0004] On the other hand, sewage sludge generated at sewage treatment plants becomes dewatered sludge during the treatment process at the sludge treatment facility, and is finally incinerated in an incinerator to reduce the volume of the dewatered sludge and discharged as ash (hereinafter referred to as "sewage sludge incineration ash"). Most of this sewage sludge incineration ash is treated to a certain extent in advance to meet landfill conditions, and then disposed of in landfills.
[0005] Furthermore, because demand for recycling blast furnace slag, incineration ash, and eco-slag is heavily influenced by economic conditions and the content of projects implemented through public investment budgets, research and technological development into more effective use of industrial waste is an urgent issue. The realization of a production environment that utilizes these effectively can contribute to the formation of a recycling-oriented society through the recycling of industrial waste, which is one of the social issues. It is also expected to lead to the extension of the life of landfill sites.
[0006] According to Non-Patent Document 1, the physical properties of currently produced blast furnace slag coarse aggregate are a specific gravity of 2.4 or more and a water absorption rate of 4.0% or less. In addition, since it is not a sintered body, the compressive strength of concrete using current blast furnace slag coarse aggregate is about 40 N / mm2 (91-day compressive strength) (Japan Steel Slag Association). The use of the sintered artificial aggregate of the present invention is mainly intended for use as a coarse aggregate for high-strength concrete, so it does not compete with the currently produced blast furnace slag coarse aggregate in terms of use. This does not hinder the utilization of recycled resources.
[0007] Methods for manufacturing sintered bodies and artificial aggregates using blast furnace slag have been proposed for some time. For example, Patent Document 1 describes an invention of a construction material in which sintered blast furnace slag is made lighter by using reinforcing fibers. Patent Document 2 describes an artificial lightweight aggregate made by granulating and molding a mixed raw material made mainly of blast furnace slag and fly ash, to which clays such as bentonite and silicon carbide are added as required, and then firing the mixed raw material. However, the strength and low water absorption properties were insufficient.
[0008] When sintering a sintering composition made mainly from industrial waste to produce artificial aggregate, it is desirable to obtain a sintered body with an average particle size of about 12 mm by low-temperature sintering at about 1200°C, with a water absorption rate of 3.0% or less and a crushing strength of more than 3000N. However, there has been no use of blast furnace slag as the main material that meets these conditions. Furthermore, we would like to widely use it in civil engineering and construction materials as an improved material that contributes to reducing the environmental load with the aim of creating a recycling-oriented society. [Prior art documents] [Non-patent literature]
[0009] [Non-Patent Document 1] Katsuro Kokufu, Technical Forum, Effective Use of Resources and Concrete, Concrete Using Slag Aggregate, Concrete Engineering, vol.34, No.3, 1996 / 3, 88-93 [Patent documents]
[0010] [Patent Document 1] Japanese Patent Application Publication No. 04-042872 [Patent Document 2] Japanese Patent Application Publication No. 09-077543 Summary of the Invention [Problem to be solved by the invention]
[0011] The present invention aims to realize a method for producing a sintered body with excellent physical properties that can be recycled from industrial waste without going through complicated processes and in a simple manufacturing method. For example, the present invention aims to realize a sintered body with a specific gravity of 2.3 or more, a water absorption rate of 4% or less, preferably 3% or less, granules with a diameter of 12 mm, a spherical shape that does not collapse, and a concrete aggregate that can reduce the water-cement ratio and contribute to improving the strength of hardened cement bodies, under relatively low temperature sintering conditions in the atmosphere. The present invention aims to realize an artificial aggregate and civil engineering and building materials with a crushing strength of 2450N or more, preferably 2700N or more, and a sintered body with a specific gravity of 2.1 to 2.3, a water absorption rate of 10% or less, and a civil engineering and building material with practical strength, under relatively low temperature sintering conditions in the atmosphere.
[0012] The artificial aggregate is a dense aggregate having a rounded shape, moderate irregularities, high strength, low water absorption, and is preferably used as a fine aggregate and a coarse aggregate for high-strength concrete.
[0013] In addition, it is desirable for the surface of the artificial aggregate to have fine irregularities to enhance adhesion between the aggregate interface and the cement paste, to enable the production of coarse aggregate with a maximum dimension of 20 mm or 25 mm, and to enable a reduction in the water-cement ratio. [Means for solving the problem]
[0014] As a result of extensive research, the inventors provide the following invention. [1] A method for producing a sintered body is provided, which comprises sintering a composition for sintering at 1190 to 1220°C, the composition comprising 100 parts by weight of ground granulated blast furnace slag (a) as a main material and 5 to 10 parts by weight of sewage sludge incineration ash (b), the cumulative weight percentage of which is 90% or more of particles having a particle size of 89 μm or less, as a melting medium for promoting densification by sintering. [2] A method for producing a sintered body is provided, which comprises sintering a composition for sintering at 1210 to 1220°C, the composition comprising 100 parts by weight of coarse blast furnace slag powder (a) as a main material and 10 to 25 parts by weight of ground eco-slag (c) having a 95% cumulative diameter of 1000 μm or less as a melting medium for promoting densification by sintering. [3] A method for producing a sintered body is provided, which comprises sintering a sintering composition containing 100 parts by weight of ground granulated blast furnace slag (a) as a main material and 10 to 25 parts by weight of ground eco-slag (e) having a 90% cumulative diameter of 57 μm or less as a melting medium for promoting densification by sintering, at 1200 to 1220°C. [4] Provided is a method for producing a sintered body, which comprises adding a binder to the sintering composition described in [1] to [3], granulating the composition or pressing the composition in a mold, and then sintering the resulting product in air. [5] Provided is a method for producing a sintered body according to any one of [1] to [4], characterized in that the sintering temperature in air is 1210°C to 1220°C, and the specific gravity after sintering is 2.3 or more and the water absorption rate is 4.0% or less.
[0015] The present invention discovered that, among various types of industrial waste, crushed eco-slag and sewage sludge incineration ash function as a melting medium that promotes densification when the main material, blast furnace slag, is fired, and that by adjusting the particle size of eco-slag and sewage sludge incineration ash in particular, even those with an average particle size larger than that of blast furnace slag can be densified by firing, which is preferable, and further promotes the utilization of industrial waste.
[0016] Blast furnace slag The general values of the chemical composition are shown in Table 1. The particle size range is preferably 1 μm to 100 μm, and the weight cumulative particle size of 100 μm or less is preferably 90% or more. The average particle size is preferably 9 to 12 μm.
[0017] [Table 1]
[0018] Sewage sludge incineration ash Table 1 also lists typical values for sewage sludge and an example of municipal waste incineration ash. Sewage sludge incineration ash is produced by incinerating dewatered sludge in a high-temperature incinerator to reduce its volume, and then collecting the resulting ash with a dust collector. The amount of K2O has a large effect. Its content range is preferably 1.9 to 3.6% by weight. The particle size of the sewage sludge incineration ash is preferably in the range of 1 μm to 300 μm, with the weight cumulative percentage of particles with a particle size of 100 μm or less being 90% or more. Representative values of the main components of sewage sludge incineration ash are shown in Table 1.
[0019] The sewage sludge incineration ash is preferably added in an amount of 5% by weight or more and 10 parts by weight or less per 100 parts by weight of blast furnace slag.
[0020] This method for producing a fired product is characterized in that the fired product is obtained by granulating or pressing in a mold, followed by firing in air. Granulating is performed by a spray drying method, a pan pelletizing method, or the like, and the shape of the mold for pressing is a flat plate, a rectangular body, a rectangular parallelepiped, or the like, which corresponds to the shape of the civil engineering and construction material.
[0021] Binder Binders are added to the various ingredients for the purpose of preventing damage to the molded product during handling during a series of manufacturing steps, from kneading and molding the ingredients to drying and roasting for baking. In addition to organic materials such as starch paste, blackstrap molasses, methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, vinyl acetate, dextrin, and pulp waste liquor, inorganic materials such as bentonite, sodium silicate, potassium silicate, and aluminum phosphate can also be used.
[0022] Water or an organic solvent can be used for granulation molding and in-mold pressure molding. Pressure molding includes standing molding under its own weight. In addition, the firing in the present invention is performed in air and does not require a reducing atmosphere. In addition, there is no prohibition on a partially reducing atmosphere in a furnace type.
[0023] The granulated product has a particle size of about 6mm to 24mm, and is suitable for use as an artificial aggregate if it has a high crushing strength when fired in air and has an appropriate specific gravity and water absorption. If it is used specifically as an artificial aggregate, this is because if the particle size is less than 6mm or more than 24mm, the fired granulated product will deviate from the particle size range of 5mm to 20mm, which is the particle size range of coarse aggregate for concrete aggregate. If it is larger than 24mm, it will take a long time to fire, and if it is smaller than 6mm, it will be impractical. In addition, since the material used to manufacture this artificial aggregate is mainly granulated blast furnace slag powder, alkali-silica reaction (ASR) is unlikely to occur even if it is used as a concrete aggregate.
[0024] A composition for firing containing blast furnace slag and a melting agent such as eco-slag or sewage sludge incineration ash was granulated or pressed in a mold and fired. The firing temperature in air is 1180°C to 1220°C, and the specific gravity after firing is preferably 2.1 to 2.4, and more preferably 2.5 or more. This is because stable firing is possible within this range.
[0025] Water absorption rate as artificial aggregate When the present invention is used as an artificial aggregate, it is preferable that the water absorption rate is 3.0% or less at a firing temperature of 1190°C to 1210°C. In the case of granular artificial aggregate, it is possible to set a low water / cement ratio, which makes it easy to prepare and control the solidified body and has a positive effect on the physical properties of the cement-solidified body.
[0026] Water absorption rate for other uses The fired body can be used for civil engineering and construction purposes other than as artificial aggregate, with a specific gravity of about 2.1 and a high water absorption rate of over 12%, allowing it to be used as a soil water retention material for greening. By reducing the water absorption rate to 3% or less, it can be used as crime prevention gravel, and when it is spread around a site, it makes it difficult for people to walk on and makes a high-pitched noise, which is expected to have a crime prevention effect. It can also be used in place of natural stone as a filter material in filtration facilities in sewage treatment facilities to further purify the treated water from the secondary sedimentation tank. In this case, the material must have high strength (3000N or more).
[0027] If the crushing strength is 2000N or more, it can be used practically as various civil engineering and construction materials, but as an artificial aggregate, it is preferable that it is 2450N or more, and particularly preferable that it is 2700N or more.
[0028] In the case of sewage sludge incineration ash, it is preferable to prepare sewage sludge incineration ash in which the cumulative weight percentage of particles with a particle size of 89 μm or less is 90% or more, add 5 to 10 parts by weight of the flux to 100 parts by weight of blast furnace slag, and burn at 1190 to 1220° C. An example of the particle size distribution of the flux is shown in FIG.
[0029] The coarse blast furnace slag powder preferably contains 10 to 25 parts by weight of crushed eco-slag with a 95% cumulative diameter of 1000 μm or less as a flux that promotes densification by firing, and is fired at 1210 to 1220° C. An example of the particle size distribution of the flux is shown in FIG.
[0030] The ground granulated blast furnace slag is preferably made to contain 10 to 25 parts by weight of ground eco-slag with a 90% cumulative diameter of 57 μm or less as a flux to promote densification by firing, and fired at 1200 to 1220° C. An example of the particle size distribution of the flux is shown in FIG. Effect of the Invention
[0031] The present invention provides a simple manufacturing method for preparing a sintering composition using blast furnace slag (a), sewage sludge incineration ash (b), coarse eco-slag particles (c), and fine eco-slag particles (e) as raw materials, without going through complicated processes. For example, when sintered under atmospheric conditions, it is possible to obtain artificial aggregate having a specific gravity of 2.3 or more, a water absorption rate of 4% or less, preferably 1% or less, and a crushing strength of 2000 N or more, preferably 2450 N or more, as well as civil engineering and construction materials with practical strength and a water absorption rate of 10% or less when sintered under atmospheric conditions.
[0032] The present invention uses ground granulated blast furnace slag as the main material, and adjusts and blends it with sewage sludge incineration ash or eco-slag, as well as mixing water and a binder, and then mixes, shapes, dries, and fires the mixture to produce artificial aggregate for concrete and other building and civil engineering materials.
[0033] The characteristics of this artificial aggregate are that it has a rounded shape, moderate unevenness, high strength, low water absorption, and is a dense aggregate. Artificial aggregate with these characteristics can be used as fine and coarse aggregate for high-strength concrete.
[0034] In addition, the surface of the artificial aggregate of the present invention has fine irregularities, which has the effect of enhancing adhesion between the aggregate interface and the cement paste. Furthermore, river gravel is round in shape and has good packing properties, so aggregates with a maximum size of 20 or 25 mm can be used, but in recent years, it has become difficult to collect such natural gravel. However, since the artificial aggregate of the present invention is manufactured in a spherical shape, it has good packing properties like gravel aggregate, and can also be manufactured with a maximum size of 20 or 25 mm. Increasing the maximum aggregate size also has the effect of reducing the water-cement ratio.
[0035] Blast-furnace cement concrete, compared with ordinary cement concrete, has a lower initial strength and a slower hydration rate, and is therefore more susceptible to the effects of low temperatures and a faster carbonation rate, so that it is necessary to increase the cover of the structure. In addition, the columns, beams, floor slabs, and walls of architectural structures are characterized by their small and thin dimensions. In response to these factors, when using blast-furnace cement concrete, it is necessary to ensure quality by making the dimensions of the parts that make up the architectural framework larger and thicker and taking a longer curing period after concrete casting. However, construction work is carried out on the premise that blast-furnace cement concrete will not be used in the framework of such buildings from the beginning. Therefore, even in ordinary cement concrete, the use of the artificial aggregate of the present invention will be a new use of recycled resources.
[0036] When the composition for firing is fired to produce an artificial aggregate, for example, a fired body with an average particle size of about 13 mm is obtained by firing at a firing temperature of about 1200°C, and the physical properties are a water absorption rate of 1.0% or less and a crushing strength of 3000 N or more. In addition, the composition for firing made only from industrial waste can be used for the artificial aggregate, which is suitable for recycling and effectively utilizing industrial waste. In addition, when made into a flat plate shape, it can be used as a civil engineering and construction material, such as a wall tile. [Brief description of the drawings]
[0037] [Figure 1] FIG. 1 is a diagram showing the particle size distribution of sewage sludge incineration ash. [Diagram 2] FIG. 2 is a diagram showing the particle size distribution of coarsely ground eco-slag. [Diagram 3] FIG. 2 is a graph showing the particle size distribution of finely pulverized eco-slag. [Figure 4] FIG. 1 is a graph showing the correlation between the water absorption rate and specific gravity of a fired body using sewage sludge incineration ash as a flux. [Diagram 5] FIG. 1 is a graph showing the correlation between the water absorption rate and specific gravity of a fired body using coarsely ground eco-slag as a flux. [Figure 6] FIG. 1 is a graph showing the correlation between the water absorption rate and specific gravity of a sintered body using finely pulverized eco-slag as a flux. [Figure 7] FIG. 1 is a graph showing the correlation between the water absorption rate and the crushing strength of a fired body using sewage sludge incineration ash as a flux. [Figure 8] FIG. 1 is a diagram showing cumulative data on particle size classification of sewage sludge incineration ash. [Figure 9] FIG. 13 is a diagram showing cumulative data of particle size classification of coarsely ground eco-slag. [Figure 10] FIG. 1 is a diagram showing cumulative data of particle size distribution of finely ground Eco-slag material. BEST MODE FOR CARRYING OUT THEINVENTION
[0038] The present invention will now be described in more detail with reference to experimental examples. First, sintered bodies containing two essential components, granulated blast furnace slag and eco-slag, or sewage sludge incineration ash, were produced.
[0039] Blast furnace slag The blast furnace slag (a) used was Esment manufactured by Esment Kanto Co., Ltd. The calculated chemical composition by fluorescent X-ray analysis is shown in Table 2. The particle size was 95% cumulative 37 μm, 76% cumulative 19 μm, and 50% cumulative 9.2 μm.
[0040] [Table 2]
[0041] The sewage sludge incineration ash used was obtained from an incineration furnace with an incineration temperature of 850°C in the freeboard section of the incineration furnace. Incineration at a temperature of 850°C reduces the emission of N2O (nitrous oxide), a greenhouse gas. The particle size distribution was approximately 266 μm maximum, with a weight cumulative particle size of 89 μm or less accounting for 90% or more (Fig. 1). Sewage sludge was incinerated in a fluidized bed incinerator, and the fly ash contained in the exhaust gas was collected in a waste heat boiler, while fine fly ash was collected in a cyclone and a dry electrostatic precipitator, and each ashes was transported by conveyor and stored in an ash hopper. The chemical composition analysis values (fluorescent X-ray analysis) of the main substances in the sewage sludge incineration ash are shown in Table 3.
[0042] [Table 3]
[0043] The eco-slag used in this application is industrial waste, including municipal solid waste and sewage sludge, incinerated in a continuous combustion stoker furnace, melted in a burner-type ash melting method, and granulated into slag. This was pulverized using a Kawasaki Heavy Industries disk-type vibration mill T-100 (chrome steel vessel).
[0044] For Eco-slag, samples were prepared with two particle size distributions as shown in Figures 2 and 3, with the grinding time adjusted. Finely ground Eco-slag was obtained by using a sieve with a mesh size of 150 μm to grind the portion that passed through the sieve in a T-100. Figure 2 shows coarsely ground Eco-slag with a 95% cumulative diameter of 1000 μm and a 100% cumulative diameter of 1930 μm. Figure 3 shows finely ground Eco-slag with a 90% cumulative diameter of 57 μm and a 100% cumulative diameter of 137 μm. Table 4 shows the chemical composition of the ground Eco-slag, expressed as oxides.
[0045] [Table 4]
[0046] Using each of the above materials, a binder and water were added in a predetermined amount (unit: g) shown in Table 5 to prepare granules (particle size 13 mm, 10 samples for each experimental example).
[0047] This was fired according to the firing pattern described above, with the upper limit of the firing temperature set between 1160° C. and 1220° C. Table 6 shows the results of physical property tests on the specific gravity and water absorption rate of the resulting fired body.
[0048] The firing temperature pattern was to increase the temperature from room temperature to 1000°C in 120 minutes, and then to the maximum firing temperature of 1160°C to 1220°C, it took 75 to 110 minutes depending on each temperature, and then the maximum firing temperature was held for 15 minutes, and the fired product was obtained by natural cooling. Hereinafter, the maximum firing temperature may be abbreviated as firing temperature. The electric furnace was a Motoyama SH-2035D.
[0049] In the present invention, the specific gravity and water absorption were measured in accordance with JIS A 1110 (Testing method for specific gravity and water absorption of coarse aggregate), using a Shimadzu analytical balance AUX120 and a specific gravity measurement kit SMK-401 (manufactured by Shimadzu Corporation). The specific gravity was measured using the SMK-401, and the density (g / cm 3 ).
[0050] The crushing strength was measured using a 5566 model (10 kN) tester manufactured by Instron Japan in accordance with JSCE-C505 (Crushing load test method for high-strength fly ash artificial aggregate). Table 6 shows the specific gravity and water absorption of the fired body.
[0051] [Table 5]
[0052] [Table 6]
[0053] [Table 7]
[0054] Effect of adding sewage sludge Change in specific gravity and water absorption of fired body Table 5 shows the composition using sewage sludge incineration ash as a flux. The specific gravity was used as a measure of the overall densification of the fired body, and the water absorption rate was used as a measure of the waterproof densification of the surface. The results are shown in Table 6. For b-1, the specific gravity changed within the range of 1.942 to 2.118 when fired at the maximum firing temperature of 1170°C to 1220°C. The water absorption rate changed within the range of 10.244% to 15.576%. For b-2, the specific gravity increased from 2.066 to 2.660 during the heating process of the maximum firing temperature, and the water absorption rate similarly decreased from 12.522% to 0.855%. In addition, the crushing strength results are shown in Table 7. The crushing strength of b-1 increased from 776N to 1051N as the maximum firing temperature increased. The highest crushing strength was 3065N for b-2 at a maximum firing temperature of 1210℃. For b-3, the highest specific gravity was 2.369 at a maximum firing temperature of 1190℃, and the specific gravity gradually decreased as the temperature increased to the maximum firing temperature. Similarly, the water absorption rate was the lowest at 2.757%, and then tended to increase. The highest crushing strength for b-3 was 2864N at a maximum firing temperature of 1180℃.
[0055] The firing results of the granulated materials b-2 and b-3, which were made by mixing sewage sludge incineration ash with blast furnace slag, showed more significant densification than b-1. In b-3, the amount of sewage sludge incineration ash was increased compared to b-2, and b-3 was superior in terms of densification up to the maximum firing temperature of 1190°C (the effect of the low firing melting temperature), but b-2 was superior in each firing up to the maximum firing temperature of 1220°C.
[0056] That is, the granules containing a mixture of blast furnace slag and sewage sludge incineration ash had a lower firing melting temperature than the granules containing only blast furnace slag, and a significant improvement in densification was observed in b-2. However, even if the amount of sewage sludge incineration ash was increased, the increase in specific gravity was relatively small, and the effect of reducing the water absorption rate peaked around b-2. This tendency was also evident when using blast furnace slag with a large particle size other than Esment, as the amount of sewage sludge incineration ash increased beyond b-3, especially at high firing temperatures of 1180°C or higher.
[0057] That is, the granules containing a mixture of blast furnace slag and sewage sludge incineration ash had a lower firing melting temperature than the granules containing only blast furnace slag, and a significant improvement in densification was observed in b-2. However, even if the amount of sewage sludge incineration ash was increased, the increase in specific gravity was relatively small, and the effect of reducing the water absorption rate peaked around b-2. This tendency was also evident when using blast furnace slag with a large particle size other than Esment, as the amount of sewage sludge incineration ash increased beyond b-3, especially at high firing temperatures of 1180°C or higher.
[0058] The results of the physical property test for crushing strength (N) are shown in Table 7. The crushing strength is the average value of the measurement results for five pieces of each granulated and fired product, and none of the maximum crushing strengths exceeded the limiter setting of 4500N.
[0059] [Table 8]
[0060] [Table 9]
[0061] [Table 10]
[0062] Effect of adding coarsely crushed eco-slag Changes in specific gravity and water absorption of fired bodies Table 8 shows the composition series C, which uses coarsely crushed Eco-slag as a flux. The specific gravity was used as a measure of the overall densification of the fired body using coarsely crushed Eco-slag as a flux, and the water absorption was used as a measure of the waterproof densification of the surface. The particle size distribution of the coarsely crushed Eco-slag is shown in Figure 2. From Table 9, only C-5 and C-6, fired at 1210°C, had a specific gravity of 2.3 or more and a water absorption of 4% or less. As the maximum firing temperature increased from 1160°C to 1220°C, the specific gravity gradually increased and the water absorption gradually decreased for C-1 to C-6 as the amount of coarsely crushed Eco-slag added increased.
[0063] Effect of adding finely ground eco-slag Change in specific gravity and water absorption of fired body Table 8 shows the composition series e using finely ground eco-slag as a flux. The specific gravity was used as a measure of the overall densification of the sintered body using finely ground eco-slag as a flux, and the water absorption rate was used as a measure of the waterproof densification of the surface. The particle size distribution of finely ground eco-slag is shown in Figure 3. From Table 10, the specific gravity of 2.3 or more and the water absorption rate of 4% or less spread from 1200℃ to 1220℃ for e-3, e-4, e-5, and e-6. The fine powdering of eco-slag was confirmed to have a wide range of the amount of addition and a lower optimum sintering temperature. In addition, as the maximum sintering temperature increased from 1160℃ to 1220℃, the specific gravity gradually increased and the water absorption rate gradually decreased with the increase in the amount of finely ground eco-slag added from e-1 to e-6. At this time, the increase in specific gravity tended to saturate, but the decrease in water absorption rate proceeded steadily. However, the water absorption rate was the lowest at 1200°C for e-6, and an exceptional increase in water absorption rate was observed only in e-6 as the firing temperature increased from 1200°C. Therefore, it can be said that the best condition is to add 25 parts by weight of Eco Slag powder to 100 parts by weight of blast furnace slag and to fire at 1200°C.
[0064] Water absorption rate-specific gravity correlation for b, c, e series Figures 4, 5, and 6 show the correlation between the water absorption rate and specific gravity of blast furnace slag calcined bodies using sewage sludge incineration ash as a flux, coarsely crushed eco-slag as a flux, and finely crushed eco-slag as a flux, respectively. All the data for water absorption rate and specific gravity used in the above table was used. The correlation coefficients between the water absorption and specific gravity of blast furnace slag calcined bodies using sewage sludge incineration ash as a flux, coarsely crushed eco-slag as a flux, and finely crushed eco-slag as a flux were -0.713, -0.992, and -0.992, respectively, and an extremely strong correlation was observed for the calcined body using crushed eco-slag.
[0065] Figure 7 shows the relationship between the water absorption rate and crushing strength of the calcined body using sewage sludge incineration ash as a flux. In another calculation, the correlation between the crushing strength y and the water absorption rate x is y = -158.39x + 3173.9, with a correlation coefficient of -0.9036 (R 2 =0.8157), which was found to be a stronger correlation than the correlation between crushing strength and specific gravity (correlation coefficient 0.757).
[0066] Therefore, ignoring the effects of the quality and quantity of the flux, the crushing strength of sintered bodies using crushed eco-slag flux can also be estimated from this relationship between crushing strength and water absorption for blast furnace slag sintered bodies, and it can be deduced that for sintered blast furnace slag bodies with a water absorption rate of 4% or less, the estimated crushing strength is generally approximately 2540N or more.
[0067] Figures 8, 9, and 10 show the cumulative data for particle size distribution of sewage sludge incineration ash, coarsely ground eco-slag, and finely ground eco-slag used as fluxes.
[0068] As a result, the recycling of industrial waste has been further enhanced by crushing or pulverizing industrial waste such as blast furnace slag, sewage sludge incineration ash, and eco-slag, forming them into granules or flat plates, and producing fired bodies.
Claims
1. A method for producing a fired body, comprising firing a composition for firing at 1190 to 1220°C, the composition containing 100 parts by weight of ground granulated blast furnace slag (a) as a main material and 5 to 10 parts by weight of sewage sludge incineration ash (b), the cumulative weight percentage of which is 90% or more of particles having a particle size of 89 μm or less, as a melting medium for promoting densification by firing.
2. A method for producing a sintered body, comprising the steps of: sintering a sintering composition containing 100 parts by weight of ground granulated blast furnace slag (a) as a main material and 10 to 25 parts by weight of ground eco-slag (c) having a 95% cumulative diameter of 1000 μm or less as a melting medium for promoting densification by sintering, at 1210 to 1220°C.
3. The method for producing a sintered body is characterized by firing a sintering composition containing 100 parts by weight of ground granulated blast furnace slag (a) as a main material and 10 to 25 parts by weight of ground eco-slag (e) having a 90% cumulative diameter of 57 μm or less as a melting medium for promoting densification by sintering at 1200 to 1220°C.
4. 4. A method for producing a fired body, comprising adding a binder to the firing composition according to any one of claims 1 to 3, granulating the composition or pressing the composition in a mold, and firing the resulting product in air.
5. 5. The method for producing a sintered body according to any one of claims 1 to 4, characterized in that the sintering temperature in the atmosphere is 1210°C to 1220°C, the specific gravity after sintering is 2.3 or more, and the water absorption rate is 4.0% or less.
Citation Information
Patent Citations
Sintered material of granulated blastfurnace slag and its production
JP1992042872A
Artificial lightweight aggregate and its production
JP1997077543A
Cited By
Method for sintering waste incineration fly ash and sludge in cooperation with iron ore
CN121222795A